In vitro Cytotoxicity of Silver Nanoparticles Incorporated in a Soft Silicone Liner - Sareh Habibzadeh; Seyyed Mostafa Fatemi (Mashhad University of Medical Sciences, 2020)
Introduction: Silver nanoparticles (SNPs) have recently been suggested to increase the antimicrobial properties of soft liner materials. However, their safety remains a matter of debate. This study aimed to evaluate the cytotoxicity of Mucopren® soft silicone liner material (Mucopren; Kettenbach, Germany) incorporated in SNPs. Methods: The SNPs with over 98% purity were added to Mucopren in 0.5, 1, 2, and 3 weight percentage (wt%) concentrations and manually homogenized. The mixture of the pieces of Mucopren plus SNPs and SNPs alone were placed in 96-well plates containing Dulbecco's Modified Eagle Medium culture, FBS, and antibiotics with L929 fibroblasts. Cell viability and biocompatibility were determined after 1, 2, and 3 days of incubation using the methylthiazol tetrazolium assay. Optical density was read by an ELISA reader at 570 nm and compared to those of positive and negative controls. Results: Among Mucopren mixed with different SNPs concentration, the cell toxicity had no significant difference in the same days, and cell toxicity decreased over time (P=0.016). The SNPs alone were less cytotoxic than Mucopren incorporated SNP samples (P>0.05). Conclusion: Within the limitations of this study, the addition of 0.5, 1, 2, and 3wt% concentrations of SNPs to Mucopren did not cause a significant change in its cell toxicity in an in vitro condition